Incisional Hernia Following Open Abdominal Aortic Aneurysm Repair: A Contemporary Review of Risk Factors and Prevention - Thuy-My Nguyen (Radcliffe Medical Media, 2020)
While the endovascular approach has been the treatment of choice for abdominal aortic aneurysm (AAA) repair in the modern era, open AAA repair remains a treatment option and may have a resurgence after the recent release of draft guidelines from the National Institute for Health and Care Excellence (NICE). Incisional hernia is a common long-term complication of open AAA repair and causes significant patient morbidity. As the number of patients undergoing open AAA repair increases, it is imperative that vascular surgeons are aware of and aim to reduce the complications associated with open surgery. This article summarises current evidence, highlighting the risk factors for incisional hernia and the modern surgical techniques that can prevent complications.